KADAR N, P, DAN K KEDELAI (Glycine max (L) Merril) YANG DIAPLIKASI AZOTOBACTER sp., MIKORIZA DAN PUPUK ORGANIK - Sabilu, Yusuf; Damhuri, Damhuri; Imran, Imran (Jurnal BioWallacea, 2015)
The purpose of this study was to determine levels of N, P, and K Soybean appliedAzotobacter sp. + Mycorrhizae and organic fertilizers. Type of experimental researchusing randomized block design (RAK) factorial design with two factors, namely thecombination of Azotobacter sp. + Mycorrhiza, consisting of 3 treatment that Azotobactersp. with a density of 103 CFU mL-1 + Mycorrhiza 30 grams, Azotobacter sp. with adensity of 104 CFU mL-1 + mycorrhiza 25 grams, Azotobacter sp. with a density of 105CFU mL-1 + Mycorrhiza 35 grams (K3); organic fertilizer factor consisted of 4 treatmentsie: without any organic fertilizer; organic fertilizer plot of 0.8 kg each equivalent to 2 tonha-1; 1.6 kg of organic fertilizer per plot equivalent to 4 ton ha-1, organic fertilizer plot of2.4 kg each equivalent to 6 ton ha-1. The results showed that the combination treatmentof Azotobacter sp. + Mycorrhiza there is not difference to the levels of nitrogen,phosphorus and potassium levels in the stem . Treatment of organic fertilizer there is asignificant difference on levels of nitrogen , phosphorus and potassium levels soybeanstem . No interaction combination of Azotobacter sp + Mycorrhiza and organic fertilizeron levels of nitrogen , phosphorus and potassium in soybean stems .Key words: Levels N , P , K Soybean, Azotobacter sp., Mycorrhizal, Organic Fertilizer.